Polymerisation, antibacterial and bioactivity properties of experimental orthodontic adhesives containing triclosan-loaded halloysite nanotubes. (February 2018) - Degrazia, Felipe Weidenbach; Genari, Bruna; Leitune, Vicente Castelo Branco; Arthur, Rodrigo Alex; Luxan, Santiago Arias; Samuel, Susana Maria Werner; Collares, Fabrício Mezzomo; Sauro, Salvatore
Graphical abstract: Highlights: TCN-HNT is a suitable filler for orthodontic dental adhesives. TCN-HNT shows in vitro inhibition of bacterial growth at 72 h. Orthodontic dental adhesives doped TCN-HNT induce mineral precipitation "Bioactivity". Incorporation of TCN-HNT in orthodontic dental adhesives improves mechanical properties. Abstract: Objective: To evaluate the immediate enamel bond strength, in situ degree of conversion and the polymerisation rate of three experimental orthodontic adhesives containing triclosan-loaded halloysite nanotubes. The antibacterial and bioactivity properties of such experimental materials were also assessed. Materials and methods: Three experimental orthodontic adhesives were formulated by incorporating triclosan-loaded halloysite nanotubes (TCN-HNT) at different concentrations (5 wt%, 10 wt% and 20 wt%) into a resin blend (Control). The maximum polymerisation rate of the tested adhesives was evaluated trough FTIR, while Raman was used to analyse the in situ degree of conversion (DC) at the bracket/enamel interface. The shear bond strength (SBS) of the enamel-bonded specimens was assessed at 24 h. The antibacterial properties of the experimental materials against S. Mutans were evaluate up to 72 h, while, their bioactivity was evaluated after 14 days of artificial saliva (AS) storage through SEM-EDS and Raman spectromicroscopy. Results: Incorporation of TCN-HNT increased the polymerisation properties without interfering with the immediate bonding properties of the experimental adhesives. All experimental adhesives containing TCN-HNT inhibited bacterial growth at 24 h, and induced mineral deposition after 14 days of AS storage. At 72 h, only the experimental system containing 20% TCN-HNT maintained such a capability. Conclusions: Adhesives doped with TCN-HNT present improved polymerisation properties and suitable bonding performance. However, only the adhesives containing TCN-HNT >10% might promote long-term antibacterial activity and reliable mineral deposition. Clinical significance: The use of adhesives containing triclosan-loaded halloysite represents a promising "smart" approach to bond orthodontic brackets and bands; these might prevent enamel demineralisation and induce enamel remineralisation during the treatment.